Portable and integrated microfluidic flow control system using off-the-shelf components towards organs-on-chip applications. - Zhu, Haoyu; Özkayar, Gürhan; Lötters, Joost; Tichem, Marcel; Ghatkesar, Murali Krishna (Biomedical Microdevices, 2023)
Organ-on-a-chip (OoC) devices require the precise control of various media. This is mostly done using several fluid control components, which are much larger than the typical OoC device and connected through fluidic tubing, i.e., the fluidic system is not integrated, which inhibits the system’s portability. Here, we explore the limits of fluidic system integration using off-the-shelf fluidic control components. A flow control configuration is proposed that uses a vacuum to generate a fluctuation-free flow and minimizes the number of components used in the system. 3D printing is used to fabricate a custom-designed platform box for mounting the chosen smallest footprint components. It provides flexibility in arranging the various components to create experiment-specific systems. A demonstrator system is realized for lung-on-a-chip experiments. The 3D-printed platform box is 290 mm long, 240 mm wide and 37 mm tall. After integrating all the components, it weighs 4.8 kg. The system comprises of a switch valve, flow and pressure controllers, and a vacuum pump to control the diverse media flows. The system generates liquid flow rates ranging from 1.5 μ Lmin - 1 to 68 μ Lmin - 1 in the cell chambers, and a cyclic vacuum of 280 mbar below atmospheric pressure with 0.5 Hz frequency in the side channels to induce mechanical strain on the cells-substrate. The components are modular for easy exchange. The battery operated platform box can be mounted on either upright or inverted microscopes and fits in a standard incubator. Overall, it is shown that a compact integrated and portable fluidic system for OoC experiments can be constructed using off-the-shelf components. For further down-scaling, the fluidic control components, like the pump, switch valves, and flow controllers, require significant miniaturization while having a wide flow rate range with high resolution.